PENGEMBANGAN FASILITAS REKREASI BERDASARKAN REFRENSI PENGUNJUNG DANAU TOBA DI PARAPAT-KABUPATEN SIMALUNGUN - Hutahaean, Theresia (Politeknik Pariwisata Medan, 2020)
This study aims to describe the efforts of the Culture and Tourism Office in developing the Lake Toba recreation area in Parapat-Simalungun Regency and to identify the driving factors in the development of recreational facilities based on the references of Lake Toba visitors in Parapat-Simalungun Regency, North Sumatra. The tools used to collect data are questionnaires and the Likert scale technique is used to analyze and describe the results of research. The results showed that the factors that encourage the development of recreational facilities based on visitors to Toba lake in Parapat, Simalungun Regency, North Sumatra is the potential of tourism objects in the Parapat-Simalungun Regency, North Sumatra, one of which is Lake Toba recreation area, tourism object development in Parapat Simalungun Regency, North Sumatra has been quite optimal both in terms of development factors, distance and location, terms of promotion and processing and others.